Glenohumeral internal rotation deficits in professional pitchers enrolled in an internal rotation stretching program - Lintner, D.; Mayol, M.; Uzodinma, O.; Jones, R.; Labossiere, D. (The American Journal of Sports Medicine, 2007)
Background: Repetitive throwing motion creates increased external rotation and decreased internal rotation in the glenohumeral joint. There is controversy regarding the contribution of osseous and soft tissue adaptations to these changes in rotation.